EFEKTIVITAS PELAKSANAAN PASAR LELANG FORWARD DI MANADO - SULAWESI UTARA - Heny Sukesi; Miftah Farid (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2009)
Auction market, particularly forward auction market has aims to develop market system through tranparency of price discovery mechanism, increase efficiency trade system and fulfill of needs among region and creating incentive for increasingproduction and quality. Those aims are important to offer solution for farmer’s classically problem, such as asymmetric commodity price information that affect to farmer’s bargaining lower than buyer’s bargaining. Therefore, there’re much region develop forward auction market including Province of North of Sulawesi. Since April 2004, the forward auction market in North Sulawesi holds in Manado. From Value of transaction view, North Sulawesi’s forward auction market seems,successful. This working paper tried tomeet comprehensive analysis of effectivity of north Sulawesi’s forward auction market, through Importance and Performance Analysis (IPA) and SWOT Analysis approach. There’re eleventh successful indicators be needed in analysis, they’re: 1) price trasparency ; 2) frequency; 3) supply gurantee for industry; 4) amount of participant; 5) incentive for increasing production and quality; 6) item of product variation; 7) price; 8) distribution chains; 9) failing of payment and delivery; 10) value of transaction and 11) completeness of supporting institution. Using IPA and SWOT analysis, can be conclude that Manado’s forward auction market still faces problems, are: there’s no supporting from other institutions forward auction market still depend on funding from DEKONSENTARSI FUND (APBN), limited of human resource in term of quality and quantity, the regulation not fully can be implemented, transaction based on trust, weak in banking gurantee, and frequency of implementation isn’t continue. One of effects of limitation in human resources interprets in stakeholder perception, there’s an indicator, potentially not hold for auction market consept. The indicator is amount of participant (seller-buyer). In Manado’s forward auction market, sellers in term of quantity have played maximally in forward auction market, but buyers in term quantity have played maximally yet. It be implied by amount of buyer lower than amount of seller, finally, the bargaining of seller/producer/farmer lower than amount of seller, finally, the bargaining. Therefore, based on SWOT analisys, there’re strategies can be proposed for improving performance of manado’s forward auction market , are: increasing coordination among institutions through develop buyer-seller networking and potency of commodity networking, making, permanenet schedule, improving quality and quantity human resources, socialize of forward auction market, monitoring of management of forward auction market system and implementing reward and punishment system.